Analisis Pengaruh Beban Kerja Petugas Aviation Security Dengan Metode Full Time Equivalent Di Bandar Udara Soekarno-Hatta - Wisandi, Pramono Sapto; Riyadi, Selamet (Universitas Mercu Buana, 2021)
Human resource planning is an activity in human resource management that is used by organizations to ensure that they have the right amount and type of human resources. This research was conducted to determine the workload of goods inspection by aviation security officers in the security check point (SCP) 1 area, Terminal 3, Soekarno-Hatta Airport with a full- time equivalent method. The results showed that the amount of workload received by the executor is normal and excessive (Overload), for the workload of employees with supervisory positions is low (Underload). The addition of employees with executive positions is 1 person each gate, and the supervisor does not have an increase in the number of employees. The optimal number of aviation security employees at each gate security check point 1 to inspect goods is 1 supervisor and 5 executors.